Математичні моделі та методи трасування променів для рендерінгу реалістичного зображення в реальному часі - Капленко, Н. В. (ХНУРЕ, 2023)
This paper investigates and compares different denoising methods for realtime ray tracing. Ray tracing, a rendering technique that simulates the physics of light, presents challenges due to its computational complexity and the noise introduced in the rendered images. Denoising methods are essential for achieving real-time performance and high-quality visuals.
Keywords: трасування променів; рендерінг реалістичного зображення; методи усунення шуму